THE INFLUENCE OF USING PICTURE CARDS TO DEVELOP STUDENT’S VOCABULARY MASTERY OF SDN 63 PAREPARE - RAFIQA RAFIQA (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2015)
The instrument of the research was multiple choice vocabulary test. In the process of collecting data, the researcher carried out an observation, interview, and some vocabulary tests. The researcher described and clarifies a phenomena or social fact by describing some variables related to examined problems or issues and formulating hypothesis into inferential levels by using statistic analysis.The result of interview from the teacher showed that teaching new vocabulary to the students is important and need precisely techniques. One way to motivate the students in learning vocabulary was using media as technique, for expample using picture.The result of some statistical analysis showed that there was significant different between post test by using picture cards and post test without using picture cards. The mean score obtain the students’ post test by without using picture cards was 73 (classified as fairly good) and the mean score of the students’ post test by using picture cards was (94.5 classified as very good